Pulmonary-Resident Memory Lymphocytes: Pivotal Orchestrators of Local Immunity Against Respiratory Infections - Humphries, Duncan C.; O’Connor, Richard A.; Larocque, Daniel; Chabaud-Riou, Martine; Dhaliwal, Kevin; Pavot, Vincent (Frontiers in Immunology, 2021)
There is increasing evidence that lung-resident memory T and B cells play a critical role in protecting against respiratory reinfection. With a unique transcriptional and phenotypic profile, resident memory lymphocytes are maintained in a quiescent state, constantly surveying the lung for microbial intruders. Upon reactivation with cognate antigen, these cells provide rapid effector function to enhance immunity and prevent infection. Immunization strategies designed to induce their formation, alongside novel techniques enabling their detection, have the potential to accelerate and transform vaccine development. Despite most data originating from murine studies, this review will discuss recent insights into the generation, maintenance and characterisation of pulmonary resident memory lymphocytes in the context of respiratory infection and vaccination using recent findings from human and non-human primate studies.